Introduction [in 2013 Annual Trends and Outlook Report] - Badiane, Ousmane; Makombe, Tsitsi; Bahiigwa, Godfrey (International Food Policy Research Institute, 2014)
As the official monitoring and evaluation (M&E) report of the Comprehensive Africa Agriculture Development Programme (CAADP), the Annual Trends and Outlook Report (ATOR) assesses trends and progress on 30 CAADP core indicators as well as the implementation agenda itself. And starting in 2011, the ATOR has featured a selected topic of strategic importance to the CAADP agenda, to help guide its planning, implementation, and dialogue processes. The 2013 ATOR contributes to the emerging debate on resilience by taking a comprehensive look at how trade can enhance food security for Africa’s poor and vulnerable through greater resilience of local food markets to environmental and economic shocks. In particular, the report focuses on the role of resilience as it relates to the capacity of local food markets to absorb the effects of economic, biophysical, or other shocks, to minimize their impact on the short or long term food security of the poor and vulnerable.